IMPLEMENTASI SISTEM INFORMASI GEOGRAFIS DALAM PENENTUAN INDEKS KESESUAIAN LAHAN TANAMAN PADI DI KOTA KUPANG MENGGUNAKAN METODE SKORING - Tiwuk Widiastuti (J-Icon : Jurnal Komputer dan Informatika, 2019)
Geographic Information System (GIS) is a special information system for managing data that has spatial information. In GIS is often used overlay techniques in merging 2 or more maps in to a unit ofland. In this research, the authors use the scoring method in determining the land suitability index. To get a unit of land done overlay on land type map, slope map, district boundary map, geological map and land cover or land use map. Scoring is done on temperature parameters, rainfall, dry moon, drainage, texture, effective depth, KTK, ground ph, n total, P2O5, K2O, slope, numbers of rock, and rock out crop. The calculationis done by scoring for each parameter based on the predetermined score class, the total of each unit of land will be used to determine the Land Suitability Index based on the classification class. The calculation result is done on 76 land (rice field and rainfed rice field). This test use Simple Linear Regression to find the closeness value between Land Suitability Index and rice produktivity. Linear correlation coeficient (r) obtained value r = 0,77 (positive correlation). The value of this correlation coefficient indicates the degree of closeness of the relationship between the Land Suitability Index and the productivity of the paddy. The value of coefficient of determination R = 0,59 = 59% indicates that 59% of the proposed variation of Y variable (paddy productivity) can be explained by X variable (Land Suitability Index) through linear relationship.